Analysis of solar radiation changes in Chinese solar greenhouses with different roof structures based on a solar radiation model - Liu, Kai; Xu, Hongjun; Li, Hong; Wu, Xiao; Sang, Siyu; Gao, Jie (International Journal of Agricultural and Biological Engineering, 2022)
Chinese solar greenhouses (CSGs) are important agricultural production facilities. Under non-artificial heating conditions, solar radiation is the only CSGs energy source. It is highly important to optimally obtain solar energy in greenhouse construction and production. In this study, a solar radiation model for solar greenhouses was adopted to explore the quantities of solar radiation in greenhouses considering different front roof forms and angles. Herein, the solar radiation amounts corresponding to five roof forms, namely, double-section arc, parabolic, oval, arc, and linear roofs, are compared and analyzed during the four solar periods (beginning of spring, vernal equinox, beginning of winter, and winter solstice). It was found that the solar radiation of oval roof greenhouses on the ground was the largest and was 4.44%-23.68% higher than that of parabolic roofs. In addition, the cumulative sum of light on the linear roof greenhouse wall is also the largest and was 6.02% to 12.08% higher than the parabolic roof greenhouse in the four solar terms. Moreover, the solar radiation in CSGs was compared with front roof angles of 25°, 30°, and 35°. It was observed that the solar radiation amount gradually increases with increasing angles. Notably, the variation at an angle of 35° influences the solar radiation of the paraboloidal CSGs ground and elliptical CSGs north wall to the greatest extent, which increased by 8.23% and 12.74%, respectively. This study confirms the role of front roof form and inclination angle in enhancing the greenhouse solar radiation level. Keywords: Chinese solar greenhouse, roof structure, roof angle, solar radiation model DOI: 10.25165/j.ijabe.20221502.6763 Citation: Liu K, Xu H J, Li H, Wu X, Sang S Y, Gao J. Analysis of Solar radiation changes in Chinese solar greenhouses with different roof structures based on a solar radiation model. Int J Agric & Biol Eng, 2022; 15(2): 221–229.